2018
DOI: 10.1186/s13643-018-0680-2
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact on health and wellbeing of interventions that foster respect and social inclusion in community-residing older adults? A systematic review of quantitative and qualitative studies

Abstract: BackgroundMany interventions have been developed to promote respect and social inclusion among older people, but the evidence on their impacts on health has not been synthesised. This systematic review aims to appraise the state of the evidence across the quantitative and qualitative literature.MethodsEligible studies published between 1990 and 2015 were identified by scanning seven bibliographic databases using a pre-piloted strategy, searching grey literature and contacting experts. Studies were included if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 113 publications
(232 reference statements)
3
76
0
4
Order By: Relevance
“…4 In time, social prescribing principles have been increasingly applied to older populations, with a view to addressing loneliness, improving physical activity levels, and mental wellbeing. 5 Understanding such diversity is important, because relevant outcomes are likely to vary according to different social prescribing schemes. Generally, programmes are aimed at addressing the social determinants of ill health, supporting patients with non-clinical root causes of poor health, or preventing disease.…”
mentioning
confidence: 99%
“…4 In time, social prescribing principles have been increasingly applied to older populations, with a view to addressing loneliness, improving physical activity levels, and mental wellbeing. 5 Understanding such diversity is important, because relevant outcomes are likely to vary according to different social prescribing schemes. Generally, programmes are aimed at addressing the social determinants of ill health, supporting patients with non-clinical root causes of poor health, or preventing disease.…”
mentioning
confidence: 99%
“…Interview responses from participants in Studies 2 and 3 emphasized these findings, with frequent mentions of connecting with others, sharing personal struggles and triumphs, and feeling joy as a result of this bonding process. These social experiences are often reported in other studies of artistic interventions (Baker et al, 2018;Clark et al, 2018;Dingle et al, 2013) and it is postulated that they help promote the positive health outcomes that are also observed among study participants (Ronzi, Orton, Pope, Valtorta, & Bruce, 2018). This was especially evident in Study 6, when social identification was measured for each group membership reported by participants.…”
Section: The Role Of Social Identitysupporting
confidence: 55%
“…Social group participation likely operates through multiple pathways to affect well-being. Indeed, other mediators of this relationship have been identified, including self-esteem and positive attitude towards aging (Ronzi et al, 2018). Along with social identity, these factors are important to consider when designing and assessing social interventions for older adults.…”
Section: Considerations For Future Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one of the studies detailed by Canedo-García involved a lifewriting workshop (Chippendale and Boltz, 2015), none of the interventions involved letter writing between different age groups, despite the dialogical and self-reflective nature of this social practice (Hall et al, 1999). Like the health-related programmes evaluated by Ronzi et al (2018) and Canedo-García et al (2017), letter writing has been found to be associated with 'physical and mental benefits across diverse samples' (Pennebaker andSeagal, 1999: 1252). More specifically, in a 'short [letter] writing campaign' involving 219 people, writing letters of gratitude was found to improve well-being and significantly decrease 'levels of depressive symptoms' (Toepfer et al, 2012: 198).…”
Section: Using Correspondence In Intergenerational Qualitative Researchmentioning
confidence: 99%